Penggunaan Hewan Sebagai Media Pembelajaran (Kajian Kisah Nabi Sulaiman A.S Dalam Al-qur'an) - Diana Safitri; Syabuddin Syabuddin; Sri Suyanta (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The story of animals in the Qur'an is one of the signs of Allah's majesty that has an important role in history. One of them is the story of Prophet Sulaiman and the ants whose story is contained in Surah An-Naml. in Surah An-Naml verses 17-19 and the dialog of the Prophet Sulaiman with Hud-hud bird in Surah An-Naml verses 20-28 are rich in meaning and wisdom that can be learned from the good side. learned from the good side. Based on the study of the verse can be taken wisdom and lessons that can be used as a learning media to conclude the educational values that are as a learning media to infer the educational values contained in it. The focus of The focus of the study is to describe the story of the prophet Solomon and the ants and the hud-hud bird and also the educational values that can be taken in Q.S.an-Naml: 1. educational values that can be taken in Q.S.an-Naml: 17-28 and how involvement of the two animals as learning media.